Prepreg, fiber-reinforced composite material, and method for producing fiber-reinforced composite material
By using matrix resin compositions of epoxy resin, aliphatic polycarbonate resin and curing agent, the problems of insufficient strength, elastic modulus and toughness of carbon fiber reinforced composite materials in the prior art are solved, and higher material performance is achieved.
Patent Information
- Application Number
- CN202380054791.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-26
- Filing Date
- 2023-07-21
- Publication Date
- 2025-03-07
AI Technical Summary
The prior art is difficult to effectively improve the strength, elastic modulus and toughness of carbon fiber reinforced composite materials.
The matrix resin composition including epoxy resin, aliphatic polycarbonate resin and a curing agent is used to improve the molecular weight and biomass degree of the resin by adjusting the component ratio and adding specific structural units, thereby improving the performance of the fiber-reinforced composite material.
A fiber-reinforced composite material that maintains toughness and significantly improves strength and elastic modulus is achieved, improving the overall performance of the material.
Smart Images

Figure BDA0005248791640000021 
Figure BDA0005248791640000031 
Figure BDA0005248791640000081
Abstract
Description
Technical Field
[0001] The invention mainly relates to a prepreg, a fiber-reinforced composite material and a method for manufacturing the fiber-reinforced composite material.
[0002] This application claims priority based on Japanese Patent Application No. 2022-119013 filed in Japan on July 26, 2022, and the contents are incorporated herein by reference. Background Art
[0003] Fiber-reinforced composite materials, which are a combination of matrix resin and reinforcing fibers, are used in a variety of applications due to their excellent lightness, rigidity, and impact resistance. In particular, carbon fiber-reinforced composite materials are used in a wide range of fields, including fishing rods, golf clubs, and other sports and leisure applications, as well as automotive and aircraft applications, due to their lightness, high strength, and high rigidity.
[0004] In the past, matrix resins for fiber-reinforced composite materials have mostly been composed of thermosetting resins, due to their excellent impregnation properties into carbon fibers and excellent physical properties after curing. In particular, matrix resins composed of epoxy resins combined with curing agents such as dicyandiamide, imidazole, and urea compounds are widely used.
[0005] In order to realize a carbon fiber reinforced composite material having higher strength and higher rigidity, a matrix resin that can effectively exhibit the characteristics of carbon fibers (high strength, high elastic modulus) is required.
[0006] Patent Document 1 proposes a composite material in which the tensile strength of reinforcing fibers is reflected by including an epoxy resin, an aromatic polycarbonate resin, dicyandiamide, and a curing accelerator.
[0007] Patent Document 2 proposes a prepreg that is practically usable and has a good balance of rigidity, toughness, and flexibility by including an aromatic polycarbonate resin that is at least partially crystallized in order to adjust the viscosity of the epoxy resin composition to a practical range.
[0008] Patent Document 3 proposes a carbon fiber reinforced thermoplastic prepreg in which the impregnation of carbon fibers with the resin is improved by using a polycarbonate resin containing at least a structural unit derived from a dihydroxy compound containing a specific structure.
[0009] Prior art literature
[0010] Patent Literature
[0011] Patent Document 1: Japanese Patent Application Laid-Open No. 2-92919
[0012] Patent Document 2: Japanese Patent Application Publication No. 2012-21112
[0013] Patent Document 3: Japanese Patent Application Publication No. 2014-133841 Summary of the invention
[0014] Problems to be solved by the invention
[0015] One object of the present invention is to provide a fiber-reinforced composite material having improved strength and elastic modulus while maintaining toughness, and a thermosetting prepreg for obtaining the fiber-reinforced composite material having improved strength and elastic modulus while maintaining toughness.
[0016] The present invention includes the following embodiments.
[0017] [1] A prepreg comprising a matrix resin composition containing at least the following components (A) to (C) and carbon fibers.
[0018] Ingredient (A): Epoxy resin
[0019] Component (B): Aliphatic polycarbonate resin
[0020] Ingredient (C): Curing agent
[0021] [2] The prepreg according to [1], comprising, as the component (B), an aliphatic polycarbonate resin having a glass transition point (Tg) of 80°C or higher.
[0022] [3] The prepreg according to [1] or [2], wherein the aliphatic polycarbonate resin of the component (B) contains a structural unit derived from a dihydroxy compound represented by the following formula (1).
[0023] [Chemistry 1]
[0024]
[0025] [4] The prepreg according to any one of [1] to [3], wherein the aliphatic polycarbonate resin of the component (B) contains structural units derived from at least one alicyclic dihydroxy compound selected from the group consisting of 1,2-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, 1,4-cyclohexanedimethanol, tricyclodecane dimethanol, pentacyclopentadecanedimethanol, 2,6-decalinedimethanol, 1,5-decalinedimethanol, 2,3-decalinedimethanol, 2,3-norbornane dimethanol, 2,5-norbornane dimethanol and 1,3-adamantanedimethanol.
[0026] [5] The prepreg according to any one of [1] to [4], comprising, as the component (C), at least one selected from the group consisting of dicyandiamides, urea compounds, acid hydrazide compounds and imidazoles.
[0027] [6] The prepreg according to [5], comprising imidazoles as the component (C).
[0028] [7] The prepreg according to any one of [1] to [6], wherein the matrix resin composition contains 5 parts by mass or more and 40 parts by mass or less of the aliphatic polycarbonate resin based on 100 parts by mass of the total epoxy resin.
[0029] [8] The prepreg according to any one of [1] to [7], wherein the matrix resin composition contains 8 parts by mass or more and 30 parts by mass or less of the aliphatic polycarbonate resin based on 100 parts by mass of the total epoxy resin.
[0030] [9] The prepreg according to any one of [1] to [8], wherein the mass ratio of the matrix resin composition to the carbon fibers ([mass of the matrix resin composition] / [mass of the carbon fibers]) is 0.25 to 9.
[0031]
[10] The prepreg according to any one of [1] to [9], wherein the carbon fiber sheets aligned in one direction are impregnated with the matrix resin composition.
[0032]
[11] The prepreg according to any one of [1] to
[10] , wherein the biomass content of the matrix resin composition is 5% or more.
[0033]
[12] A fiber-reinforced composite material obtained by curing the prepreg according to any one of [1] to
[11] .
[0034]
[13] A method for producing a fiber-reinforced composite material, comprising pressing the prepreg according to any one of [1] to
[11] at 100°C to 160°C.
[0035]
[14] A prepreg obtained by impregnating a carbon fiber substrate with a matrix resin composition comprising at least an epoxy resin, a polycarbonate resin and an imidazole, wherein the polycarbonate resin contains a structural unit derived from a dihydroxy compound represented by the following formula (1).
[0036] [Chemistry 2]
[0037]
[0038]
[15] The prepreg according to
[14] , comprising a polycarbonate resin having a glass transition point (Tg) of 80°C or higher as the component (B).
[0039]
[16] The prepreg according to
[14] or
[15] , wherein the polycarbonate resin further comprises a structural unit derived from at least one alicyclic dihydroxy compound selected from the group consisting of 1,2-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, 1,4-cyclohexanedimethanol, tricyclodecane dimethanol, pentacyclopentadecanedimethanol, 2,6-decalinedimethanol, 1,5-decalinedimethanol, 2,3-decalinedimethanol, 2,3-norbornane dimethanol, 2,5-norbornane dimethanol and 1,3-adamantanedimethanol.
[0040]
[17] The prepreg according to any one of
[14] to
[16] , wherein the matrix resin composition contains 5 parts by mass or more and 30 parts by mass or less of the polycarbonate resin based on 100 parts by mass of the total epoxy resin.
[0041]
[18] The prepreg according to any one of
[14] to
[17] , wherein the carbon fiber base material is a carbon fiber sheet aligned in one direction.
[0042]
[19] The prepreg according to any one of
[14] to
[18] , wherein the biomass content of the matrix resin composition is 5% or more.
[0043] Effects of the Invention
[0044] According to one embodiment of the present invention, a fiber-reinforced composite material having improved strength and elastic modulus while maintaining toughness, and a prepreg for obtaining a fiber-reinforced composite material having improved strength and elastic modulus while maintaining toughness can be obtained. DETAILED DESCRIPTION
[0045] [Prepreg]
[0046] One embodiment of the present invention relates to a prepreg. The prepreg of the embodiment includes a matrix resin composition containing at least the following components (A) to (C) and carbon fibers.
[0047] Ingredient (A): Epoxy resin
[0048] Component (B): Aliphatic polycarbonate resin
[0049] Ingredient (C): Curing agent
[0050] [Matrix resin composition]
[0051] The matrix resin composition comprises at least the above-mentioned component (A), component (B) and component (C). The matrix resin composition may further comprise other thermoplastic resins and additives. The matrix resin composition contained in the prepreg may be a thermosetting matrix resin composition, which forms a cross-linked structure by heating.
[0052] The biomass content of the matrix resin composition is preferably 5% or more, more preferably 10% or more, and even more preferably 20% or more.
[0053] The biomass content of the matrix resin composition can be calculated from the biomass content of the raw materials, the input ratio during the blending, and the input ratio during the synthesis reaction and polymerization reaction. 14 The obtained resin composition was directly analyzed by C determination method.
[0054] based on 14 The biomass content can be determined by radiocarbon determination according to ASTM-D6866 ( 14 C) obtained by determination 14 The C content is calculated. It is known that carbon dioxide in the atmosphere contains 14 C, so plants that grow by absorbing carbon dioxide from the atmosphere also contain a certain amount of 14 C. On the other hand, it is also known that fossil fuels contain almost no 14 C. Therefore, by measuring the total carbon atoms contained 14 The proportion of C can be used to calculate the biomass degree.
[0055] [Ingredients (A)]
[0056] The epoxy resin of component (A) is not particularly limited as long as it is a compound having an epoxy group. Examples of such epoxy resins include: bisphenol A type epoxy resins; bisphenol F type epoxy resins; heterocyclic epoxy resins (e.g., epoxy resins containing a ring structure derived from isosorbide, a triisocyanurate ring, or an oxazolidone ring in the molecule); novolac type epoxy resins derived from cresol novolac, phenol novolac, or bisphenol A novolac; glycidylamine type epoxy resins (e.g., triglycidylaminophenol, tetraglycidyldiaminodiphenylmethane, diglycidylaniline, diglycidyltoluidine, tetraglycidylxylenediamine; glycidyl esters derived from polycarboxylic acids (e.g., dimer acid, trimer acid, isophthalic acid, terephthalic acid, phthalic acid, hydrophthalic acid); Type epoxy resin; bisphenol S type epoxy resin; for example, hydroquinone type epoxy resin derived from resorcinol, catechol, hydroquinone, dihydroanthracene; for example, aromatic type epoxy resin derived from dihydroanthrahydroquinone, dihydroxydiphenyl ether, thiodiphenol, dihydroxynaphthalene, trihydroxyphenylmethane, tetrahydroxyphenylethane; bisphenoxyethanol fluorene type epoxy resin; bisphenol fluorene type epoxy resin; biscresol fluorene type epoxy resin. In addition, for example, a resin having an oxirane ring produced by oxidation of an allyl group can also be used. As the epoxy resin, bisphenol A type epoxy resin, bisphenol F type epoxy resin, heterocyclic type epoxy resin, condensed ring type epoxy resin, novolac type epoxy resin, glycidylamine type epoxy resin, and glycidyl ester type epoxy resin are preferred.
[0057] As component (A), a liquid epoxy resin or a solid epoxy resin can be mixed. The liquid epoxy resin is an epoxy resin that is liquid at 25° C. The liquid epoxy resin mainly helps to improve the solubility of component (B) and other thermoplastic resins and improve the strength, elastic modulus, and heat resistance of the cured product of the matrix resin composition.
[0058] The viscosity of the liquid epoxy resin at 25°C is preferably 500 Pa·s or less, more preferably 300 Pa·s or less. In addition, it is preferably 0.1 Pa·s or more. For example, it may be 0.1 Pa·s or more and 500 Pa·s or less, or it may be 0.1 Pa·s or more and 300 Pa·s or less. If the viscosity is set to this range, the workability of the epoxy resin composition can be improved.
[0059] The viscosity can be measured by applying periodic deformation (strain) to a sample using a rotational rheometer and detecting the stress and phase difference generated thereby.
[0060] The amount of the liquid epoxy resin is preferably set to 5 parts by mass or more relative to 100 parts by mass of all epoxy resins contained in the matrix resin composition. The lower limit of the amount of the liquid epoxy resin is more preferably 8 parts by mass, more preferably 15 parts by mass, particularly preferably 25 parts by mass, and most preferably 28 parts by mass. In addition, the upper limit of the amount of the liquid epoxy resin is preferably 80 parts by mass, more preferably 75 parts by mass, and more preferably 70 parts by mass. The above upper and lower limits can be combined arbitrarily. For example, it can be more than 5 parts by mass and less than 80 parts by mass, it can be more than 8 parts by mass and less than 75 parts by mass, or it can be more than 15 parts by mass and less than 70 parts by mass. When the amount of the liquid epoxy resin is more than the lower limit, the dissolution of component (B) and other thermoplastic resin components becomes easy, and the strength and elastic modulus of the obtained resin cured product are excellent. On the other hand, if the amount of the liquid epoxy resin is less than the upper limit, a resin cured product with excellent toughness can be obtained.
[0061] In addition, by adding a solid epoxy resin, the viscosity at room temperature can be increased, and the prepreg becomes easy to handle. Solid epoxy resin refers to an epoxy resin that is solid at room temperature and becomes liquid by heating. The solid epoxy resin is preferably an epoxy resin with a softening point of 50°C or above. From the perspective of excellent toughness of the cured resin, the softening point is preferably above 55°C, and more preferably above 60°C. On the other hand, from the perspective of being able to properly maintain the heat resistance of the cured resin, being able to obtain a prepreg with excellent drapability (mold shape tracking), and being able to obtain a fiber-reinforced composite material without voids, it is preferably below 150°C, and more preferably below 145°C. The above upper and lower limits can be combined arbitrarily. For example, it can be above 50°C and below 150°C, it can be above 55°C and below 150°C, or it can be above 60°C and below 140°C.
[0062] The amount of solid epoxy resin is preferably set to less than 95 mass parts relative to 100 mass parts of all epoxy resins contained in the matrix resin composition. The upper limit of the amount of solid epoxy resin is more preferably 90 mass parts, more preferably 80 mass parts, particularly preferably 70 mass parts, and most preferably 60 mass parts. In addition, the lower limit of the amount of solid epoxy resin is preferably 5 mass parts, more preferably 8 mass parts, and more preferably 10 mass parts. The above upper and lower limits can be combined arbitrarily. For example, it can be more than 5 mass parts and less than 80 mass parts, it can be more than 8 mass parts and less than 95 mass parts, or it can be more than 10 mass parts and less than 90 mass parts. If the amount of solid epoxy resin is within the above range, it is possible to obtain the viscosity of the prepreg, the drapability (mold shape followability), and the voids in the prepreg without impregnation poorly, strength and elastic modulus and heat resistance, and a fiber reinforced composite material with excellent toughness.
[0063] When component (B) or other thermoplastic resins are dissolved in the epoxy resin in advance, the epoxy resin can be dissolved smoothly by using a bisphenol epoxy resin or a glycidylamine epoxy resin as the epoxy resin, and the viscosity of the obtained dissolved product can be easily adjusted. These epoxy resins can be used alone or in combination.
[0064] When it is desired to improve the heat resistance of the fiber-reinforced composite material, a novolac-type epoxy resin or a glycidylamine-type epoxy resin can be used.
[0065] When it is desired to increase the biomass content of the fiber-reinforced composite material, glycidyl ester epoxy resins derived from biomass-derived acids, glycidyl ether epoxy resins produced from natural or non-edible biomass, and heterocyclic epoxy resins derived from biomass-derived isosorbide can be used.
[0066] In addition, epoxy resins using epichlorohydrin derived from glycerol, which is a byproduct of biofuel, can also be preferably used. Epichlorohydrin may have a skeleton derived from natural products or biomass, or may have a skeleton derived from non-natural products or non-biomass, and may be added appropriately for use.
[0067] When it is desired to improve the toughness of the fiber-reinforced composite material, a heterocyclic epoxy resin containing an oxazolidinone ring or a condensed ring epoxy resin containing an isosorbide structure can be used.
[0068] On the other hand, an epoxy resin obtained by pre-reacting the aforementioned liquid epoxy resin with the polyamine described later can also be used. Such an epoxy resin has a tertiary amine structure in the epoxy resin, and thus shows a tendency to be excellent in reactivity. Furthermore, by using an aromatic polyamine as the polyamine, an epoxy resin having strength, elastic modulus and reactivity can be obtained, and thus it can be used according to the required prepreg properties.
[0069] [Ingredient (B)]
[0070] By including component (B) in the matrix resin composition, a fiber-reinforced composite material having excellent strength and elastic modulus while maintaining toughness can be obtained. An aliphatic polycarbonate resin is a resin that does not contain an aromatic structure in its molecular chain. By being aliphatic, the aliphatic polycarbonate resin can be prevented from being deteriorated by the curing agent contained in the matrix resin composition in the prepreg, and the deterioration of the operability of the prepreg during storage can be prevented.
[0071] Aliphatic polycarbonate resins can be produced by conventionally known methods, for example, solution polymerization using phosgene, melt polymerization with a carbonic acid diester, preferably a melt polymerization method in which a dihydroxy compound is reacted with a carbonic acid diester having a lower toxicity in the presence of a polymerization catalyst.
[0072] As the carbonic acid diester, a generally known material can be used, for example, substituted diphenyl carbonates such as diphenyl carbonate and ditolyl carbonate, dimethyl carbonate, diethyl carbonate, and di-tert-butyl carbonate can be exemplified. Diphenyl carbonate and substituted diphenyl carbonates are preferred, and diphenyl carbonate is more preferred.
[0073] As the polymerization catalyst (ester exchange catalyst) in the melt polymerization method, conventionally known materials can be used, for example, one or both of an alkali metal compound and an alkaline earth metal compound can be used. Basic compounds such as basic boron compounds, basic phosphorus compounds, basic ammonium compounds, and amine compounds can be used together with one or both of the alkali metal compound and the alkaline earth metal compound as an auxiliary. It is particularly preferred to use only one or both of the alkali metal compound and the alkaline earth metal compound.
[0074] As the dihydroxy compound, a compound having a structure represented by the following formula (1), an alicyclic dihydroxy compound, or other dihydroxy compounds can be used. From the viewpoint of not lowering the Tg of the fiber-reinforced composite material, the aliphatic polycarbonate resin preferably contains a structural unit derived from a dihydroxy compound represented by the following formula (1).
[0075] [Chemistry 3]
[0076]
[0077] The component ratio (molar ratio) of the structural units constituting the aliphatic polycarbonate resin can be selected in any ratio. Regarding the ratio, as "structural units derived from dihydroxy compounds represented by formula (1): structural units derived from alicyclic dihydroxy compounds", it is preferably 1:99 to 99:1 (mol%), and more preferably 10:90 to 90:10 (mol%). By using structural units derived from dihydroxy compounds represented by formula (1), it is easy to increase the molecular weight of the resin, and Tg also becomes higher, so the toughness of the fiber-reinforced composite material can be improved. By using structural units derived from alicyclic dihydroxy compounds, coloring and water absorption can be suppressed, and the reduction of mechanical properties caused by dimensional changes in the fiber-reinforced composite material can be suppressed.
[0078] In addition, other dihydroxy compounds may be contained, for example, in order to improve flexibility, reduce viscosity, or adjust polarity, within a range that does not significantly impair performance.
[0079] As the compound represented by formula (1), isosorbide, isomannide and isoidide including their isomers can be cited, and one can be used alone or in combination of two or more. From the perspective of economy and availability, isosorbide derived from sorbitol produced from starch, which is abundant in resources and easily available, is preferred.
[0080] As the alicyclic hydroxy compound, a conventionally known raw material can be used, for example, a compound containing a five-membered ring structure or a six-membered ring structure can be used. In addition, the six-membered ring structure can be fixed into a chair shape or a boat shape by a covalent bond. As the alicyclic hydroxy compound, for example, 1,2-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, 1,4-cyclohexanedimethanol, tricyclodecane dimethanol, pentacyclopentadecanedimethanol, 2,6-decahydronaphthalene dimethanol, 1,5-decahydronaphthalene dimethanol, 2,3-decahydronaphthalene dimethanol, 2,3-norbornane dimethanol, 2,5-norbornane dimethanol, 1,3-adamantanedimethanol, and they can also be compounds modified with various substituents. That is, the aliphatic polycarbonate resin of the component (B) is preferably contained in a structural unit derived from at least one alicyclic dihydroxy compound selected from the group consisting of 1,2-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, 1,4-cyclohexanedimethanol, tricyclodecane dimethanol, pentacyclopentadecanedimethanol, 2,6-decalinedimethanol, 1,5-decalinedimethanol, 2,3-decalinedimethanol, 2,3-norbornane dimethanol, 2,5-norbornane dimethanol and 1,3-adamantanedimethanol.
[0081] Furthermore, examples of the alicyclic hydroxy compound include 2,2-bis(4-hydroxyphenyl)propane (bisphenol A), 2,2-bis(4-hydroxy-3,5-dimethylphenyl)propane, 2,2-bis(4-hydroxy-3,5-dimethylphenyl)propane, 2,2-bis(4-hydroxy-(3,5-diphenyl)phenyl)propane, 2,2-bis(4-hydroxy-3,5-dibromophenyl)propane, 2,2-bis(4-hydroxyphenyl)pentane, 2,4'-dihydroxy-diphenylmethane, bis(4-hydroxyphenyl)methane, bis(4-hydroxy-5-nitrophenyl)methane, 1,1-bis(4-hydroxyphenyl)ethane, 3,3-bis(4-hydroxyphenyl)ethane, and 1,1-bis(4-hydroxyphenyl)ethane. The present invention also includes dihydroxy compounds obtained by hydrogenating aromatic bisphenols to hydrogenate aromatic nuclei, such as bis(4-hydroxyphenyl)pentane, 1,1-bis(4-hydroxyphenyl)cyclohexane, bis(4-hydroxyphenyl)sulfone, 2,4'-dihydroxydiphenylsulfone, bis(4-hydroxyphenyl)sulfide, 4,4'-dihydroxydiphenyl ether, 4,4'-dihydroxy-3,3'-dichlorodiphenyl ether, 4,4'-dihydroxy-2,5-diethoxydiphenyl ether, 9,9-bis(4-(2-hydroxyethoxy)phenyl)fluorene, 9,9-bis(4-(2-hydroxyethoxy-2-methyl)phenyl)fluorene, 9,9-bis(4-hydroxyphenyl)fluorene, and 9,9-bis(4-hydroxy-2-methylphenyl)fluorene. In addition, the dihydroxy compounds may include unhydrogenated aromatic bisphenols in view of process economics when hydrogenating aromatic nuclei. In this case, the content of the unhydrogenated aromatic bisphenol in 100% by mass of the dihydroxy compound is preferably 10% by mass or less, more preferably 5% by mass or less, and even more preferably 1% by mass or less.
[0082] The alicyclic hydroxy compound may be used alone or in combination of two or more. Preferred are cyclohexanedimethanol, tricyclodecanedimethanol, adamantanediol, and pentacyclopentadecanedimethanol. In terms of availability and ease of handling, 1,4-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, 1,2-cyclohexanedimethanol, and tricyclodecanedimethanol are preferred.
[0083] Examples of other dihydroxy compounds include ethylene glycol, 1,3-propylene glycol, 1,2-propylene glycol, 1,4-butylene glycol, 1,3-butylene glycol, 1,2-butylene glycol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,12-dodecanediol, hydrogenated dilinoleyl glycol, hydrogenated dioleyl glycol and other linear aliphatic dihydroxy compounds, 1,3-butylene glycol, 2-methyl-1,3-propanediol, neopentyl glycol, 2-ethyl-1,6-hexanediol, 2,2- Branched-chain aliphatic dihydroxy compounds such as 4-trimethyl-1,6-hexanediol, 3-methyl-1,5-pentanediol, 2-n-butyl-2-ethyl-1,3-propanediol, 2,2-diethyl-1,3-propanediol, 2,4-diethyl-1,5-pentanediol, 1,2-hexanediol, 1,2-octanediol, 2-ethyl-1,3-hexanediol, 2,3-diisobutyl-1,3-propanediol, 2,2-diisopentyl-1,3-propanediol, and 2-methyl-2-propyl-1,3-propanediol; oxyalkylene glycols such as diethylene glycol, triethylene glycol, and tetraethylene glycol.
[0084] As the linear aliphatic dihydroxy compound, 1,3-propylene glycol, 1,4-butylene glycol, 1,6-hexanediol, 1,9-nonanediol and 1,10-decanediol are preferred, and as the branched aliphatic dihydroxy compound, 3-methyl-1,5-pentanediol, 2-n-butyl-2-ethyl-1,3-propylene glycol, 2,2-diethyl-1,3-propylene glycol and 2,4-diethyl-1,5-pentanediol are preferred.
[0085] The glass transition point (Tg) of the aliphatic polycarbonate resin is preferably 80°C or more, more preferably 90°C or more. The method described in the examples can be applied to the determination of the glass transition point. If it is 80°C or more, when molding the prepreg, the resin exudation caused by the rapid decrease in viscosity during heating can be suppressed, and the glass transition point (Tg) of the fiber-reinforced composite material can be suppressed from decreasing and the mechanical properties under heating can be suppressed. It should be noted that when component (B) is crystalline, the glass transition point refers to the softening point.
[0086] The glass transition point (Tg) can be adjusted to the above range by adjusting the types of monomers used in the production of the aliphatic polycarbonate resin, adjusting the blending ratio thereof, adjusting the polymerization temperature, adjusting the amount of additives added, and the like.
[0087] It is known that the degree of polymerization (specifically, molecular weight) is a physical property related to the glass transition point (Tg) of component (B), and if the degree of polymerization increases to a certain level or more, it can be expressed by reduced viscosity. Except for polycarbonate diols having a low glass transition point and a low degree of polymerization (low molecular weight), the degree of polymerization (specifically, molecular weight) of component (B) is measured by reduced viscosity.
[0088] The lower limit of the reduced viscosity of the aliphatic polycarbonate resin is usually 0.2dL / g, preferably 0.3dL / g, and more preferably 0.35dL / g. Thus, in addition to suppressing the reduction of the viscosity and heat resistance of the obtained matrix resin composition at room temperature, the fracture toughness and mechanical properties of the matrix resin composition after curing are also improved. In addition, the upper limit of the reduced viscosity is usually 1.2dL / g, preferably 1dL / g, and more preferably 0.8dL / g. Thus, dissolution in liquid resin becomes easy. The determination of the reduced viscosity can be applied to the method described in the embodiment.
[0089] The above upper and lower limits may be arbitrarily combined, for example, 0.2 dL / g to 1.2 dL / g, 0.3 dL / g to 1 dL / g, or 0.35 dL / g to 0.8 dL / g.
[0090] As the overall amount of component (B), from the viewpoint of improving the toughness, strength and elastic modulus of the fiber-reinforced composite material, it is preferably 1 part by mass or more, more preferably 3 parts by mass or more, and further preferably 5 parts by mass or more relative to 100 parts by mass of the total epoxy resin component. From the viewpoint of the impregnation of carbon fiber and the operability when laminating prepreg, the overall amount of component (B) is preferably 40 parts by mass or less, more preferably 30 parts by mass or less, further preferably 20 parts by mass or less, and particularly preferably 14 parts by mass or less relative to 100 parts by mass of the total epoxy resin component.
[0091] The above-mentioned upper and lower limits can be combined arbitrarily. For example, relative to 100 mass parts of all epoxy resin components, it can be more than 1 mass part and less than 40 mass parts, it can be more than 1 mass part and less than 30 mass parts, it can be more than 3 mass parts and less than 20 mass parts, it can also be more than 5 mass parts and less than 14 mass parts.
[0092] From the viewpoint of improving the toughness, strength and elastic modulus of the fiber-reinforced composite material, the total amount of component (B) is preferably 0.5% by mass or more, more preferably 5% by mass or more, in 100% by mass of the matrix resin composition. From the viewpoint of impregnation into the reinforcing fibers and operability when laminating the prepreg, the total amount of component (B) is preferably 35% by mass or less, more preferably 30% by mass or less, and particularly preferably 20% by mass or less, relative to 100% by mass of the matrix resin composition.
[0093] The upper and lower limits mentioned above may be combined arbitrarily. For example, in 100% by mass of the matrix resin composition, it may be 0.5% by mass or more and 35% by mass or less, 0.5% by mass or more and 30% by mass or less, or 5% by mass or more and 20% by mass or less.
[0094] When the fiber-reinforced composite material is used for sports applications, automobile components, etc., the total amount of component (B) may be 8% by mass or more and 40% by mass or less relative to 100% by mass of the matrix resin composition in order to improve fracture toughness, impact absorption, viscosity characteristics during processing, etc.
[0095] The component (B) contained in the matrix resin composition of the present invention can be analyzed with high accuracy by generally known analysis methods or by a combination of these analysis methods. For example, GPC (gel permeation chromatography) analysis and solvent extraction after freeze-crushing can be combined.
[0096] According to infrared absorption spectroscopy, the absorption of carbonyl groups derived from carbonate bonds is at 1760-1780 cm -1 Peaks were observed nearby.
[0097] According to NMR analysis, a signal of the structural unit of component (B) is obtained, and therefore, whether or not the component (B) is incorporated into the polymer structure can be determined from the signal pattern, shift, etc.
[0098] Since GC-MS can detect structural units by thermal decomposition of the reaction, the accuracy can be improved by comparing the NMR signal with a compound corresponding to the structural unit as a standard.
[0099] In addition, the molecular weight, reduced viscosity and glass transition point of component (B) can be obtained from the broadening of the signal of H adjacent to the carbonate group. In this case, the accuracy can be improved by using a similar substance as a standard.
[0100] [Ingredient (C)]
[0101] Component (C) is a curing agent, and the component (C) is not particularly limited as long as it is a compound that helps the curing of the epoxy group of component (A). The curing agent preferably includes at least one curing agent selected from the group consisting of dicyandiamide, urea compounds, imidazoles and acid hydrazide compounds. Among these, imidazoles are particularly preferred from the perspective of increasing the glass transition point of the cured product and the molded plate and shortening the molding time. In addition, the above curing agents can be used alone or in combination of two or more. As other curing agents, amines can also be included.
[0102] As the dicyandiamide, for example, what can be used is a product obtained by preliminarily reacting dicyandiamide with the epoxy resin listed as the component (A).
[0103] The dicyandiamides may be used alone or in combination of two or more.
[0104] Examples of the urea compound include aromatic ureas in which a urea group is bonded to an aromatic ring and aliphatic ureas in which a urea group is bonded to an aliphatic chain.
[0105] Examples of the aliphatic urea include urea represented by the following formula (2).
[0106] R 1 -NH-CO-NR 2 R 3 ···(2)
[0107] (In formula (2), R 1 represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms, R 2 and R 3 Each independently represents an alkyl group having 1 to 6 carbon atoms. )
[0108] Examples of the alkyl group include a methyl group, an ethyl group, a propyl group, a butyl group, an isopropyl group, and a tert-butyl group. A methyl group and an ethyl group are particularly preferred.
[0109] Examples of the aliphatic urea include dimethyl urea obtained from isophorone diisocyanate and dimethylamine, dimethyl urea obtained from meta-xylylenediisocyanate and dimethylamine, and dimethyl urea obtained from hexamethylene diisocyanate and dimethylamine.
[0110] Examples of the aromatic urea include aromatic dimethyl ureas such as phenyl dimethyl urea, methylene bis(phenyl dimethyl urea) and toluene bis(dimethyl urea).
[0111] Examples of the aromatic dimethyl urea include 4,4'-methylenebis(phenyl dimethyl urea) (MBPDMU), 3-phenyl-1,1-dimethyl urea (PDMU), 3-(3,4-dichlorophenyl)-1,1-dimethyl urea (DCMU), 3-(3-chloro-4-methylphenyl)-1,1-dimethyl urea, and 2,4-bis(3,3-dimethylureido)toluene (TBDMU). In terms of curing acceleration capability and imparting heat resistance to a cured resin, phenyl dimethyl urea, methylene bis(phenyl dimethyl urea), and toluene bis(dimethyl urea) are more preferred, and in terms of ease of supply, ease of curing in a short time, and the ability to impart high heat resistance to a cured resin, DCMU, PDMU, and TBDMU are particularly preferred.
[0112] The urea compounds may be used alone or in combination of two or more.
[0113] As the imidazoles, for example, imidazole derivatives, imidazole adducts, inclusion imidazoles, microcapsule-type imidazoles, and imidazole compounds coordinated with stabilizers can be used. Imidazoles have nitrogen atoms with unshared electron pairs in their structures, which activate epoxy groups and thus accelerate curing.
[0114] Examples of the imidazole derivative include 2-methylimidazole, 2-ethyl-4-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-phenylimidazole, 1-benzyl-2-methylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazolium trimellitate, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-phenylimidazole, 2,4 -diamino-6-(2'-methylimidazolyl-(1'))-ethyl-s-triazine, 2,4-diamino-6-(2'-undecylimidazolyl-(1'))-ethyl-s-triazine, 2,4-diamino-6-(2'-ethyl-4-methylimidazolyl-(1'))-ethyl-s-triazine, 2,4-diamino-6-(2'-methylimidazolyl-(1'))-ethyl-s-triazine isocyanuric acid adduct, 2-phenylimidazole isocyanuric acid adduct, 2-methylimidazole isocyanuric acid adduct, 1-cyanoethyl-2-phenyl-4,5-bis(2-cyanoethoxy)methylimidazole, 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole.
[0115] Imidazole adducts, inclusion imidazoles, microencapsulated imidazoles, or imidazole compounds coordinated with stabilizers are compounds modified from these imidazole derivatives. They suppress the activity by treating imidazole derivatives with adducts, using inclusion treatment with foreign molecules, microencapsulation treatment, or coordination with stabilizers, and exhibit excellent service life in low temperature regions and high curing and curing acceleration capabilities.
[0116] The imidazoles may be used alone or in combination of two or more.
[0117] Examples of the acid hydrazide compound include aromatic hydrazide compounds and aliphatic hydrazide compounds.
[0118] Examples of the aromatic hydrazide compound include salicylic acid hydrazide, benzoic acid hydrazide, 1-naphthoic acid hydrazide, terephthalic acid dihydrazide, isophthalic acid dihydrazide, 2,6-naphthoyl dihydrazide, 2,6-pyridine dihydrazide, 1,2,4-benzene trimellitic acid hydrazide, 1,4,5,8-naphthoyl tetrahydrazide, and pyromellitic acid tetrahydrazide.
[0119] Examples of the aliphatic hydrazide compound include formic hydrazide, acetic hydrazide, propionic acid hydrazide, oxalic acid dihydrazide, malonic acid dihydrazide, succinic acid dihydrazide, glutaric acid dihydrazide, adipic acid dihydrazide, pimelic acid dihydrazide, sebacic acid dihydrazide, 1,4-cyclohexane dihydrazide, tartaric acid dihydrazide, malic acid dihydrazide, iminodiacetic acid dihydrazide, N,N'-hexamethylenebissemicarbazide, citric acid trihydrazide, nitriloacetic acid trihydrazide, cyclohexanetricarboxylic acid tri ... dihydrazide compounds having a hydantoin skeleton, preferably a valine hydantoin skeleton (a skeleton in which the carbon atoms of the hydantoin ring are substituted with isopropyl groups), such as 3-bis(hydrazinocarbonylethyl)-5-isopropylhydantoin, tris(1-hydrazinocarbonylmethyl)isocyanurate, tris(2-hydrazinocarbonylethyl)isocyanurate, tris(2-hydrazinocarbonylethyl)isocyanurate, tris(3-hydrazinocarbonylpropyl)isocyanurate, and bis(2-hydrazinocarbonylethyl)isocyanurate.
[0120] The acid hydrazide compounds may be used alone or in combination of two or more.
[0121] The amines are not particularly limited, and examples thereof include chain aliphatic polyamines (e.g., diethylenetriamine, tetraethylenepentamine, hexamethylenediamine, 1,3-pentanediamine, 2-methylpentamethylenediamine), alicyclic polyamines (e.g., isophoronediamine, 4,4'-methylenebiscyclohexylamine, 4,4'-methylenebis(2-methylcyclohexylamine), bis(aminomethyl)norbornane, 1,2-cyclohexanediamine, 1,3-bisaminomethylcyclohexane), aromatic polyamines (e.g., isophoronediamine, 4,4'-methylenebiscyclohexylamine, 4,4'-methylenebis(2-methylcyclohexylamine), bis(aminomethyl)norbornane, 1,2-cyclohexanediamine, 1,3-bisaminomethylcyclohexane), Dimethylamine, 4,4'-methylenedianiline, 4,4'-methylenebis(2-methylaniline), 4,4'-methylenebis(2-ethylaniline), 4,4'-methylenebis(2-isopropylaniline), 4,4'-methylenebis(2-chloroaniline), 4,4'-methylenebis(2,6-dimethylaniline), 4,4'-methylenebis(2,6-diethylaniline), 4,4'-methylenebis(2-isopropyl-6-methylaniline), 4,4'-methylenebis (2-ethyl-6-methylaniline), 4,4'-methylenebis(2-bromo-6-ethylaniline), 4,4'-methylenebis(N-methylaniline), 4,4'-methylenebis(N-ethylaniline), 4,4'-methylenebis(N-sec-butylaniline), 4,4'-diaminodiphenyl sulfone, 3,3'-diaminodiphenyl sulfone, 4,4'-cyclohexylidene diphenylamine, 4,4'-(9-fluorenylidene) diphenylamine, 4,4'-(9-fluorenylidene) bis(N-methylaniline aniline), 4,4'-diaminobenzanilide, 4,4'-oxydianiline, 2,4-bis(4-aminophenylmethyl)aniline, 4-methyl-m-phenylenediamine, 2-methyl-m-phenylenediamine, N,N'-di-sec-butyl-p-phenylenediamine, 2-chloro-p-phenylenediamine, 2,4,6-trimethyl-m-phenylenediamine, 2,4-diethyl-6-methyl-m-phenylenediamine, 4,6-diethyl-2-methyl-m-phenylenediamine, 4,6-dimethyl-m-phenylenediamine, trimethylenebis(4-aminobenzoate).
[0122] These amines can be used as adducts or block forms.
[0123] As the overall amount of component (C), since the epoxy resin can be fully cured, it is preferably 0.5 parts by mass or more, more preferably 1.0 parts by mass or more relative to 100 parts by mass of the total epoxy resin components. In addition, from the aspect of excellent storage stability, it is preferably 40 parts by mass or less, more preferably 20 parts by mass or less, and particularly preferably 10 parts by mass or less relative to 100 parts by mass of the total epoxy resin components.
[0124] The upper and lower limits mentioned above may be combined arbitrarily. For example, the amount may be 0.5 to 40 parts by mass, 0.5 to 20 parts by mass, or 1.0 to 10 parts by mass, relative to 100 parts by mass of the total epoxy resin component.
[0125] When a dicyandiamide is used, a urea compound or an imidazole may be used in combination from the viewpoint of workability during molding.
[0126] When a dicyandiamide and a urea compound are used in combination, the mass ratio (dicyandiamide / urea compound) can be set to 1 to 2, for example.
[0127] When dicyandiamide and imidazoles are used together, the mass ratio (dicyandiamide / imidazoles) can be set to 0.01 to 1, for example.
[0128] When dicyandiamide, urea compound and imidazole are used together, the mass ratio (imidazole / urea compound) can be set to 0.01-10.
[0129] When an acid hydrazide compound is used, a urea compound or an imidazole may be used in combination.
[0130] When the acid hydrazide compound and the urea compound are used together, the mass ratio (acid hydrazide compound / urea compound) can be set to 1.0 to 2.0, for example.
[0131] When the acid hydrazide compound and the imidazoles are used together, the mass ratio (acid hydrazide compound / imidazoles) can be set to, for example, 0.01 to 1.0.
[0132] [Thermoplastic resin]
[0133] The matrix resin composition contains a thermoplastic resin (referring to a resin other than the component (B)) as another component, thereby being able to improve moldability by controlling polarity, suppressing layer separation, inducing layer separation, and controlling melt attraction.
[0134] Examples of the thermoplastic resin include, but are not limited to, polyamide, polyester, polycarbonate other than component (B), polyethersulfone, polyphenylene ether, polyphenylene sulfide, polyetheretherketone, polyetherketone, polyimide, polytetrafluoroethylene, polyether, polyolefin, polyarylate, polysulfone, polyacrylonitrile styrene, polystyrene, polyacrylonitrile, polymethyl methacrylate, ABS (acrylonitrile-butadiene-styrene copolymer), AES (acrylonitrile-ethylene-propylene rubber-styrene copolymer), ASA (acrylonitrile-acrylic rubber-styrene copolymer), polyvinyl chloride, polyvinyl formal resin, phenoxy resin, and resins obtained by block copolymerization of these thermoplastic resins.
[0135] It should be noted that an aromatic polycarbonate resin may be contained within a range that does not significantly impair the performance, but from the viewpoint of the strength and elastic modulus of the obtained fiber-reinforced composite material, it is preferred that the aromatic polycarbonate resin is not contained.
[0136] From the viewpoint of suppressing the resin bleeding during molding, polyethersulfone, polyvinyl formal resin, and phenoxy resin are more preferred.
[0137] The thermoplastic resin may be used alone or in combination of two or more.
[0138] The content of the thermoplastic resin can be adjusted within a range of 30 parts by mass or less relative to 100 parts by mass of the total epoxy resin. From the viewpoint of suppressing the flow of the resin during molding, the total amount of the component (B) and the thermoplastic resin is preferably adjusted to 1 part by mass or more and 30 parts by mass or less relative to 100 parts by mass of the total epoxy resin, and more preferably 2 parts by mass or more and 25 parts by mass or less.
[0139] [additive]
[0140] Examples of the additives include stabilizers, inhibitors, flame retardants, release agents, inorganic fillers, organic fillers, organic pigments, and inorganic pigments.
[0141] The stabilizer and inhibitor can be selected from various viewpoints. For example, from the viewpoint of inhibiting hydrolysis, linear carbodiimide compounds and cyclic carbodiimide compounds can be mentioned. From the viewpoint of stabilizing the curing agent, stabilizers using inclusion compounds and stabilizers using boric acid compounds can be mentioned.
[0142] As flame retardants, phosphorus-based flame retardants (such as phosphorus-containing epoxy resins, red phosphorus, phosphazene compounds, phosphates, and phosphate esters) can be cited, and as inorganic flame retardants, hydrated metal compound systems (such as aluminum hydroxide, magnesium hydroxide), inorganic oxides (such as antimony compounds, zinc borate, zinc stannate, Mo compounds, ZrO, zinc sulfide, zeolite, and titanium oxide nanofiller systems) can be cited.
[0143] Examples of the release agent include silicone oil, wetting and dispersing agents, defoaming agents, air release agents, natural waxes, synthetic waxes, metal salts of linear fatty acids, amides, esters, and paraffins.
[0144] Examples of the inorganic filler include powders of crystalline silica, amorphous silica, fused silica, calcium silicate, alumina, calcium carbonate, talc, barium sulfate, and the like; glass fibers; and short carbon fibers.
[0145] Examples of the organic filler include cellulose fiber, flux fiber, ramie fiber, hemp fiber, and wood powder. The fiber of the organic filler may be in the form of continuous fiber, nanofiber, or milled fiber, and may be subjected to surface hydrophilic treatment or hydrophobic treatment.
[0146] The additives may be used alone or in combination of two or more.
[0147] In the case of wanting to suppress resin exudation during molding, crystalline silica and amorphous silica can be used. The smaller the particle size of crystalline silica or amorphous silica, the more the inhibitory effect of resin exudation is improved. From the viewpoint of safety, amorphous silica is more preferred. In addition, in the case of wanting to increase the biomass degree, amorphous silica manufactured from natural raw materials can be used.
[0148] [Method for producing matrix resin composition]
[0149] The matrix resin composition can be obtained, for example, by mixing the above-mentioned components. Examples of a method for mixing the components include a method using a mixer (eg, a three-roll mill, a planetary mixer, a kneader, a homogenizer, or a homodisper).
[0150] The matrix resin composition can be used for the production of a prepreg by, for example, impregnating a carbon fiber base material as described below. The viscosity of the matrix resin composition at 30° C. can be 100 to 1,000,000 Pa·s.
[0151] [Carbon Fiber]
[0152] The carbon fibers exist in the prepreg as a carbon fiber matrix (aggregate of carbon fibers). The carbon fibers may be arranged in a single direction or randomly.
[0153] As the form of the carbon fiber substrate, for example, a carbon fiber fabric, a carbon fiber nonwoven fabric, and a sheet (UD sheet) in which long fibers of carbon fiber are aligned in one direction can be cited. From the viewpoint of being able to mold a fiber-reinforced composite material with high specific strength and specific elastic modulus, the carbon fiber is preferably a UD sheet, and from the viewpoint of easy handling, the carbon fiber is preferably a carbon fiber fabric.
[0154] The unit area weight of the carbon fiber substrate can be set to 10g / m 2 Above and 4000g / m 2 the following.
[0155] The prepreg may contain reinforcing fibers other than carbon fibers, and for example, glass fibers, aramid fibers, and boron fibers may be used.
[0156] The fiber diameter of the carbon fiber can be set to 3 μm to 15 μm.
[0157] The number of carbon fibers in the carbon fiber bundle used in the carbon fiber base material is preferably 1,000 to 70,000.
[0158] From the viewpoint of the rigidity of the fiber-reinforced composite material, the carbon fiber strand tensile strength is preferably 1.5 to 9 GPa.
[0159] From the viewpoint of the rigidity of the fiber-reinforced composite material, the carbon fiber strand tensile modulus is preferably 150 to 260 GPa.
[0160] The strand tensile strength and strand tensile elastic modulus of carbon fibers are values measured in accordance with JIS R7601:1986.
[0161] [Prepreg Manufacturing Method]
[0162] The prepreg is obtained, for example, by impregnating a carbon fiber base material with the above-mentioned matrix resin composition.
[0163] As a method for impregnating a carbon fiber substrate with a matrix resin composition, examples include, but are not limited to, a wet method in which the matrix resin composition is dissolved in a solvent (e.g., methyl ethyl ketone, methanol) to reduce the viscosity and then impregnated into the carbon fiber substrate; and a hot melt method (dry method) in which the matrix resin composition is reduced in viscosity by heating and then impregnated into the carbon fiber substrate.
[0164] The wet method is a method in which the carbon fiber base material is immersed in a solution of the matrix resin composition, then pulled out, and the solvent is evaporated using an oven or the like.
[0165] The hot melt method includes: a method of directly impregnating a carbon fiber substrate with a matrix resin composition that has been reduced in viscosity by heating; and a method of temporarily applying a matrix resin composition to the surface of a substrate such as release paper to prepare a film in advance, overlapping the prepared films from both sides or one side of the carbon fiber substrate, and impregnating the carbon fiber substrate with the resin by heating and pressurizing. The coating layer obtained by applying the coating layer to the surface of a substrate such as release paper can be used directly in the hot melt method in an uncured state, or can be used in the hot melt method after the coating layer is cured.
[0166] The hot melt method is preferred because substantially no solvent remains in the prepreg.
[0167] The temperature when the matrix resin composition is impregnated into the carbon fiber substrate can be 50°C to 120°C, and is preferably 10°C or more lower than the glass transition point of the component (B) from the viewpoint of suppressing degradation of the component (B).
[0168] From the viewpoint of improving the mechanical properties of the fiber-reinforced composite material and the adhesion to carbon fibers, the content of the matrix resin composition in the prepreg is preferably 15% to 50% by mass, more preferably 20% to 45% by mass, and even more preferably 25% to 40% by mass, relative to the total mass of the prepreg.
[0169] [Fiber-reinforced composite materials]
[0170] The fiber-reinforced composite material is obtained by curing the prepreg. That is, the fiber-reinforced composite material comprises a cured product of the matrix resin composition contained in the prepreg and carbon fibers. As a fiber-reinforced composite material, a cured product of a laminated body formed by stacking more than two prepregs can also be made. The fiber-reinforced composite material can be obtained, for example, by molding in the following method: after stacking more than two prepregs, a pressure is applied to the obtained laminated body while the matrix resin composition is heated and cured.
[0171] As molding methods, there can be cited, but are not limited to, for example, press molding, autoclave molding, bag compression molding, tape wrapping, internal pressure molding, sheet winding molding, RTM (Resin Transfer Molding) in which the epoxy resin composition is impregnated into filaments of reinforcing fibers, preforms and cured to obtain molded products, VaRTM (Vacuum assisted Resin Transfer Molding), filament winding, and RFI (Resin Film Infusion).
[0172] As a molding method that maximizes the characteristics of the matrix resin composition, autoclave molding is preferred. Press molding is preferred from the viewpoints of utilizing the characteristics of the matrix resin composition, high productivity, and facilitating the production of a high-quality fiber-reinforced composite material.
[0173] When a fiber-reinforced composite material is manufactured by press molding, it is preferred to place a prepreg or a preformed product made by stacking prepregs in a mold pre-adjusted to a curing temperature and heat and pressurize the prepreg or preformed product to cure the prepreg or preformed product. The temperature in the mold during press molding is preferably 100 to 160° C. In addition, it is preferred to cure the prepreg or preformed product under a condition of 1 to 15 MPa for 1 to 20 minutes.
[0174] Example
[0175] The present invention is further described in detail by way of examples.
[0176] (Raw materials used)
[0177] [Ingredients (A)]
[0178] jER828: liquid bisphenol A type epoxy resin, epoxy equivalent 189 g / eq, manufactured by Mitsubishi Chemical Corporation.
[0179] SR GreenPoxy28: liquid bisphenol A type epoxy resin, epoxy equivalent 180 g / eq, biomass content 28%, manufactured by Sicomin.
[0180] jER604: Liquid glycidylamine epoxy resin, epoxy equivalent 120 g / eq, manufactured by Mitsubishi Chemical Corporation.
[0181] ·EPICLON N-670: solid cresol novolac type epoxy resin, epoxy equivalent 210g / eq, DIC Corporation.
[0182] [Ingredient (B)]
[0183] · B-1: structural unit derived from isosorbide / structural unit derived from 1,4-cyclohexanedimethanol=70 / 30 mol%, Tg: 120° C., reduced viscosity 0.43 dl / g, biomass degree 59%, DURABIO D7340R manufactured by Mitsubishi Chemical Corporation.
[0184] · B-2: structural unit derived from isosorbide / structural unit derived from tricyclodecane dimethanol=70 / 30 mol%, Tg: 124°C, reduced viscosity 0.35 dl / g, biomass degree 53%, DURABIO T7430 IR manufactured by Mitsubishi Chemical Corporation.
[0185] [Thermoplastic resin]
[0186] ·YP-70: Bisphenol A type / F type copolymer phenoxy resin, manufactured by Nippon Steel Chemical Materials Co., Ltd.
[0187] [Ingredient (C)]
[0188] DCMU: 3-(3,4-dichlorophenyl)-1,1-dimethylurea, DCMU-99 manufactured by Hodogaya Chemical Co., Ltd.
[0189] DICY: dicyandiamide, jER CURE DICY15 manufactured by Mitsubishi Chemical Corporation.
[0190] · 2MZA-PW: 2,4-diamino-6-[2'-methylimidazole-(1')]-ethyl-s-triazine, manufactured by Shikoku Chemical Industry Co., Ltd.
[0191] · 2MAOK-PW: 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine isocyanuric acid adduct, manufactured by Shikoku Chemical Industry Co., Ltd.
[0192] PN-40: imidazole adduct, softening temperature 110°C, Amicure PN-40 manufactured by Ajinomoto Fine Chemicals Co., Ltd.
[0193] [additive]
[0194] L-07N: a composition containing a borate ester compound, manufactured by Shikoku Chemical Industry Co., Ltd.
[0195] · Ethical Silica: Amorphous silicon dioxide, husk Ethical Silica made by MIT.
[0196] [Carbon Fiber]
[0197] Carbon fiber: PAN-based carbon fiber, manufactured by Mitsubishi Chemical Corporation, Pyrofil TR50S15L.
[0198] (Manufacture of resin sheets)
[0199] The matrix resin composition was sandwiched between glass plates and placed in a hot air oven, and then heated from room temperature to 130° C. at 2° C. / min. After reaching 130° C., the temperature was further maintained for 120 minutes to obtain a resin plate having a thickness of 2 mm.
[0200] (Manufacturing of prepreg and molded sheets)
[0201] After a resin film is produced by applying a matrix resin composition at a specified weight per unit area onto release paper using a roll coater, the obtained resin film is overlapped on both sides of a carbon fiber sheet composed of carbon fibers adjusted to a specified weight per unit area, and the resin is impregnated into the carbon fibers using a heated roller to obtain a unidirectional prepreg.
[0202] The obtained prepreg was cut into 300 mm × 300 mm and stacked in such a way that the fiber directions were all oriented in the same direction, thereby obtaining a laminate. The laminate was heated at 2°C / min under a pressure of 0.04 MPa in an autoclave, maintained at 80°C for 60 minutes, and then heated at 2°C / min under a pressure of 0.6 MPa, maintained at 130°C for 90 minutes to be heat-cured to obtain a molded plate with a thickness of 2.0 to 2.2 mm.
[0203] (Measurement of glass transition point (Tg))
[0204] The glass transition point of the aliphatic polycarbonate resin was measured using a differential scanning calorimeter DSC6220 (manufactured by SII NanoTechnology Co., Ltd.).
[0205] About 10 mg of the resin sample was placed in an aluminum pan manufactured by the company and sealed. Under a nitrogen flow of 50 mL / min, the temperature was raised from 30°C to 200°C at a heating rate of 20°C / min. After maintaining the temperature for 3 minutes, it was cooled to 30°C at a rate of 20°C / min. It was maintained at 30°C for 3 minutes and then heated to 200°C at a rate of 20°C / min again. Based on the DSC data obtained in the second heating, the temperature of the intersection of the straight line obtained by extending the baseline on the low temperature side to the high temperature side and the tangent line drawn at the point where the gradient of the curve of the step-shaped change part of the glass transition reaches the maximum, that is, the extrapolated glass transition starting temperature, was obtained and used as the glass transition point.
[0206] The glass transition point of the resin plate and the molded plate was measured using a rheometer (TA Instruments Japan, ARES-RDS) at a measurement frequency of 1 Hz and a heating rate of 5°C / min, and the peak of tanδ was taken as the glass transition point. The test piece was made of a 2 mm thick resin plate processed into a length of 55 mm and a width of 12.5 mm.
[0207] (Determination of reduced viscosity)
[0208] The reduced viscosity of the aliphatic polycarbonate resin is measured by the following method.
[0209] The polycarbonate resin was dissolved in a solvent to prepare a polycarbonate solution having a concentration of 0.60 g / dl. Methylene chloride was used as the solvent.
[0210] The reduced viscosity was measured using an Ubbelohde viscometer "DT-504 automatic viscometer" manufactured by Chuo Rika Co., Ltd. at a temperature of 20.0°C ± 0.1°C. The relative viscosity ηrel was calculated from the solvent passage time t0 and the solution passage time t by the following formula (α), and the specific viscosity ηsp (unit: g·cm) was calculated from the relative viscosity ηrel by the following formula (β): -1 ·sec -1 ). It should be noted that η0 in formula (β) is the viscosity of the solvent. Then, the reduced viscosity η (η=ηsp / c) is calculated by dividing the specific viscosity ηsp by the concentration c (g / dL) of the polycarbonate solution. The higher the value, the larger the molecular weight.
[0211] ηrel=t / t0···(α)
[0212] etasp=(eta-eta0) / eta0=etarel-1···(β)
[0213] (Bending test of resin plate)
[0214] Six test pieces of 8 mm in width and 60 mm in length were cut out from a resin plate of 2 mm in thickness, and strength and elastic modulus were measured under the following conditions using a universal testing machine (Instron, Instron 5965), and the average value of the six pieces was obtained. It should be noted that elongation at break and elongation at yield were also measured in some tests. Here, the high values of elongation at break and elongation at yield indicate excellent toughness.
[0215] Crosshead speed: 2 mm / min, span: the thickness of the cured resin plate was measured and set to (thickness×16) mm.
[0216] (Bending test of formed plate)
[0217] The obtained molded plate was cut into the following shapes to prepare test pieces.
[0218] 0° bending test specimen: length 100mm x width 12.7mm, L / d = 40
[0219] 90° bending test specimen: length 60mm x width 12.7mm, L / d = 16
[0220] The test piece for the 0° bending test was processed so that the carbon fibers were parallel to the longitudinal direction of the test piece, and the test piece for the 90° bending test was processed so that the carbon fibers were substantially orthogonal to the longitudinal direction of the test piece.
[0221] The obtained test piece was subjected to a universal testing machine manufactured by Instron Corporation, and a 3-point bending fixture (indenter R = 5 mm, support R = 3.2 mm) was used under an environment of a temperature of 23°C and a humidity of 50% RH, and the distance between the supports (L) was set to 40 in the 0° bending test and to 16 in the 90° bending test. In addition, the ratio of the distance between the supports (L) to the thickness (d) of the test piece was set to L / d, and a bending test was performed under the condition of a crosshead speed (speed component) = (L2×0.01) / (6×d), and the strength, elastic modulus, and fracture strain at 0° and 90° were obtained.
[0222] (Examples 1 to 17, Comparative Examples 1 to 3)
[0223] According to the composition described in Tables 1 to 3, jER828 or SR Green Poxy 28 and a curing agent were weighed into a container so that the mass ratio of the solid component to the liquid component was 1:2, and stirred to obtain a mixture. The obtained mixture was further finely mixed using a three-roll mill (Inoue Seisakusho Co., Ltd.) to obtain a curing agent masterbatch.
[0224] Next, jER828 or SR GreenPoxy28, excluding the components used in the curing agent masterbatch, and the thermoplastic resin or component (B) in the composition described in Tables 1 to 3 were weighed into a flask, and the temperature was raised to 180°C in stages using an oil bath and mixed uniformly. Then, after slowly cooling to 100°C, the unmixed epoxy resin described in Tables 1 to 3 was weighed and mixed uniformly. Finally, it was slowly cooled to about 60°C, the above-mentioned curing agent masterbatch was added, and the mixture was mixed uniformly to obtain a matrix resin composition.
[0225] Using the obtained matrix resin composition, a resin plate is obtained according to the manufacturing method of the resin plate. The obtained resin plate was subjected to a bending test and a glass transition point (Tg) measurement, and the results are shown in Tables 1 to 3. It should be noted that the elongation at break and the elongation at yield obtained based on the bending test of the resin plate of Comparative Example 1 are 8.5% and 7.9%, respectively, those of Example 1 are 7.9% and 7.6%, respectively, and those of Example 2 are 8.2% and 7.7%, respectively. In addition, those elongations of Comparative Example 3 are 8.4% and 7.4%, respectively, those of Example 13 are 8.6% and 6.9%, respectively, and those of Example 16 are 8.2% and 6.5%, respectively.
[0226] Next, according to the manufacturing method of the prepreg and the molded plate, the prepreg and the molded plate are obtained. It should be noted that the fiber unit area weight, the resin unit area weight, the resin content of the obtained prepreg and the number of laminated sheets of the molded plate during the manufacture of the prepreg are shown in Table 4. The obtained molded plate was subjected to a bending test and a glass transition point (Tg) measurement, and the results are shown in Table 4. It should be noted that the fiber volume content (Vf) is converted to 60% in Comparative Example 2 and Examples 1, 11, and 12, and Vf is converted to 50% in Comparative Example 3 and Example 16.
[0227] [Table 1]
[0228]
[0229] [Table 2]
[0230]
[0231] [Table 3]
[0232]
[0233] [Table 4]
[0234]
[0235] As shown in Tables 1 to 3, by comparing Examples 1 to 12 with Comparative Examples 1 to 2, and by comparing Examples 13 to 17 with Comparative Example 3, the strength and elastic modulus of the resin plate are improved by including component (B) in the matrix resin composition. In addition, by comparing the elongation at break and the elongation at yield of Comparative Example 1 with those of Examples 1 and 2, and by comparing these elongations of Comparative Example 3 with those of Examples 13 and 16, it can be seen that the strength and elastic modulus are improved while maintaining the toughness of the resin plate. It should be noted that the glass transition point of the resin plate in Examples 1 to 12 in which component (C) contains imidazoles is high, and the operability during molding is excellent.
[0236] Furthermore, as shown in Table 4, by comparing Examples 1, 11 and 12 with Comparative Examples 1 to 2, and by comparing Example 16 with Comparative Example 3, it can be seen that by making the matrix resin composition contain component (B), the strength and elastic modulus of the obtained molded plate are improved while maintaining toughness. In particular, in the 90° bending test, the strength and elastic modulus are significantly improved by the matrix resin composition containing component (B). The 90° bending test depends not only on the performance of the matrix resin composition, but also on the adhesion of the interface between the carbon fiber and the matrix resin. That is, it can be said that by including component (B) in the matrix resin composition, in addition to the strength and elastic modulus of the matrix resin composition, the adhesion between the carbon fiber and the matrix resin is also improved. It should be noted that the glass transition point of the molded plate in Examples 1 and 12 in which component (C) contains imidazoles is high, and the operability during molding is excellent.
[0237] It should be noted that by replacing jER828 used in the examples with, for example, SR GreenPoxy29 (liquid bisphenol A epoxy resin, epoxy equivalent 186 g / eq, biomass degree 30%, manufactured by Sicomin), the biomass degree of Examples 1 to 13, 16, and Comparative Examples 1 to 3 can be increased by 15 to 20%.
[0238] Possibility of Industrial Application
[0239] The prepreg and fiber-reinforced composite materials of the embodiments described above can be used for various structural materials including bodies or parts of transportation equipment (including automobiles, motorcycles and bicycles), sports equipment, leisure equipment, parts of home appliances, parts of agricultural machinery, building materials, etc.
Claims
1. A prepreg comprising a matrix resin composition containing at least the following components (A) to (C) and carbon fibers, Ingredient (A): Epoxy resin, Component (B): aliphatic polycarbonate resin, Component (C): Curing agent. 2 . The prepreg according to claim 1 , wherein the component (B) comprises an aliphatic polycarbonate resin having a glass transition point (Tg) of 80° C. or higher.
3. The prepreg according to claim 1 or 2, wherein the aliphatic polycarbonate resin of the component (B) comprises a structural unit derived from a dihydroxy compound represented by the following formula (1): [Chemistry 1] 4. The prepreg according to claim 3, wherein the aliphatic polycarbonate resin of the component (B) further comprises a structural unit derived from at least one alicyclic dihydroxy compound selected from the group consisting of 1,2-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, 1,4-cyclohexanedimethanol, tricyclodecane dimethanol, pentacyclopentadecanedimethanol, 2,6-decalinedimethanol, 1,5-decalinedimethanol, 2,3-decalinedimethanol, 2,3-norbornane dimethanol, 2,5-norbornane dimethanol and 1,3-adamantanedimethanol. The prepreg according to claim 1 , comprising, as the component (C), at least one selected from the group consisting of dicyandiamides, urea compounds, acid hydrazide compounds and imidazoles. The prepreg according to claim 5 , comprising imidazoles as the component (C). 7 . The prepreg according to claim 1 , wherein the matrix resin composition comprises 5 parts by mass or more and 40 parts by mass or less of the aliphatic polycarbonate resin relative to 100 parts by mass of the total epoxy resin. 8 . The prepreg according to claim 1 , wherein the matrix resin composition comprises 8 parts by mass or more and 30 parts by mass or less of the aliphatic polycarbonate resin relative to 100 parts by mass of the total epoxy resin. 9 . The prepreg according to claim 1 , wherein a mass ratio of the matrix resin composition to the carbon fibers, that is, [mass of the matrix resin composition] / [mass of the carbon fibers], is 0.25 to 9.
10. The prepreg according to claim 1 or 2, wherein the carbon fiber sheets aligned in one direction are impregnated with a matrix resin composition. 11 . The prepreg according to claim 1 or 2 , wherein the biomass content of the matrix resin composition is 5% or more.
12. A fiber-reinforced composite material obtained by curing the prepreg according to claim 10.
13. A method for producing a fiber-reinforced composite material, comprising pressing the prepreg according to claim 10 at 100°C to 160°C.
14. A prepreg obtained by impregnating a carbon fiber substrate with a matrix resin composition comprising at least an epoxy resin, a polycarbonate resin and imidazoles, wherein the polycarbonate resin comprises a structural unit derived from a dihydroxy compound represented by the following formula (1): [Chemistry 2] 15 . The prepreg according to claim 14 , comprising, as the component (B), a polycarbonate resin having a glass transition point (Tg) of 80° C. or higher.
16. The prepreg according to claim 14 or 15, wherein the polycarbonate resin further comprises a structural unit derived from at least one alicyclic dihydroxy compound selected from the group consisting of 1,2-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, 1,4-cyclohexanedimethanol, tricyclodecane dimethanol, pentacyclopentadecanedimethanol, 2,6-decalinedimethanol, 1,5-decalinedimethanol, 2,3-decalinedimethanol, 2,3-norbornane dimethanol, 2,5-norbornane dimethanol and 1,3-adamantanedimethanol. 17 . The prepreg according to claim 14 , wherein the matrix resin composition comprises 5 parts by mass or more and 30 parts by mass or less of the polycarbonate resin relative to 100 parts by mass of the total epoxy resin. 18 . The prepreg according to claim 14 , wherein the carbon fiber base material is a carbon fiber sheet aligned in one direction. 19 . The prepreg according to claim 14 , wherein the biomass content of the matrix resin composition is 5% or more.
Citation Information
Patent Citations
Resin composition for composite material, intermediate material and composite material
JP1990092919A
Prepreg and composite material thereof
JP2012021112A
Prepreg and composite material
JP2014133841A
Cited By
Nano indium-iron microcrystalline adhesive and curing process
CN120442199A
Carbon fiber connecting glue and curing process
CN122648042A